The Potency of Refugia Plants in Increasing Insect Diversity of Rice Fields in Padang Pariaman, West Sumatra - Widya Nawir; Novri Nelly; Yaherwandi Yaherwandi (Jurnal Proteksi Tanaman)
Utilization of bunga kertas (Zinnia elegans), jengger ayam (Celosia sp.), and marigold (Marigold erecta) as refugia plants and conservation media for predators and parasitoids among farmers is still not optimal. Planting refugia plants around rice plants affects the diversity and evenness index. Insect diversity and evenness index describes the level of stability and balance of the cropping ecosystem. This study was conducted to determine the effect of planting Zinnia elegans, Celosia sp., and Marigold erecta as refugia on the diversity and evenness index of insects and their potential as a medium for the conservation of predators and parasitoids. in the expanse of organic rice fields in Batang Anai sub-district, Padang Pariaman district, West Sumatra from May to July 2020. Insect collection was carried out in treatment plots covering an area of ??48 m2 and identified in the Bioecology Laboratory, Faculty of Agriculture, Unand in Padang. The types and populations of insects in rice planted with refugia plants, especially Celosia sp., were higher than those of Zinnia elegans, Marigold erecta and control. Celosia sp plants have a higher index of insect diversity and evenness than Zinnia elegans, Marigold erecta plants. The ratio or comparison of pest populations, predators and parasitoids on Celosia sp plants was lower than that of Zinnia elegans, Marigold erecta dan control plants.